Modern experimental prose through the prism of Psychoanalytical theories - Lončar Vujnović, Mirjana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The balance between the subjective and the objective perspectives in experimental prose must be accomplished in order to achieve the effect of intensive reflective and spiritual reality. Deleuze and Guattari take the method of William Burroughs and James Joyce as examples of the so- called “butchered text method“ which refers to the temporal-spatial perspective. Furthermore, they mention Nietzsche’s interlocking of “eternal return of the present as something that opinion does not know” and the theory of Stephen Mallarme, who combines well known, fragmented style with alchemical dream. According to him, the primary purpose of the modern text is to get closer to the reader so that any reader can interpret it in his own way. Trying to demystify scientific fantasy of objectivity, Lacan does not attribute impersonality and exteriority to art, but science and theory. According to him, a text without the influence of psychological factors, which make both life and characters more realistic, is not art. The connection between the external world and a man is expressed through a mirror, which Lacan tentatively calls “imago”. Imago of the outside world or one’s appearance is present in hallucinations or dreams, always reflecting the internal condition of the individual, its fragility (senility) or its fair projection, thereby making this “subjective-objective” relationship unbreakable.